Emotional experience elicited by direct electrical stimulation: Case series and literature review - Guiliang Hao; Xiaoxia Zhou; Hao Yan; Xueyuan Wang; Liang Qiao; Duanyu Ni; Wei Shu; Tao Yu (Epilepsia Open, 2023)
Abstract Objective The cortical representation of emotions is complex, and cortical mapping of emotional experience is incomplete. We aimed to contribute to cortical mapping of emotional experience. Methods Clinical data from 400 patients with medically refractory epilepsy who underwent stereo‐electroencephalography implantation for localization of the epileptogenic zone at the Beijing Institute of Functional Neurosurgery between October 2015 and June 2021 were collected retrospectively. Furthermore, we reviewed studies that described cortical mapping of emotional experience through electrical cortical stimulation (ECS). Affective responses similar to ictal aura and electrode contacts located in the SOZ were excluded to investigate emotional experiences in normal brain regions. Results Emotional experiences were evoked by stimulation at 10 electrode contacts in the seven patients, including five contacts that evoked mirth and excitement, one contact that evoked calmness, three contacts that evoked fear, and one contact that evoked sadness. In addition, 21 studies that evaluated emotional experiences in response to cortical electrical stimulation were reviewed. Emotions were distributed in the amygdala, hippocampus, temporal lobe, frontal lobe, insula, frontal operculum, parietal operculum, and cingulate cortex. Significance We provided additional evidence that brain regions including the amygdala, hippocampus, temporal lobe, frontal lobe, insula, frontal operculum, parietal operculum, and cingulate cortex were associated with emotional experience.